REFLECTING ON PEDAGOGICAL CHALLENGES EXPERIENCED WHEN BIPOC INSTRUCTORS TEACH COURSES FOCUSED ON RACE AND RACIALIZATION - Rose, Janine (PUPIL: International Journal of Teaching, Education and Learning, 2024)
Existing research has explored the challenges that University instructors experience when incorporating anti-racist pedagogical strategies in their teaching. However, there is limited exploration of the emotional labor that BIPOC instructors experience when teaching students about the experiences of the populations to which they belong. This presentation extends this research by exploring the experiences of a Black identified and immigrant instructor in a course that explores the experiences of Black immigrants in Canadian cities. The research is based on a self-reflective autoethnography that documents one instructor’s experience with teaching a Black experience course at a Canadian institution. The research shows that strategies such as incorporating projects and course readings that celebrate the contributions and accomplishments of the population under study is one way of dealing with the challenges associated with teaching difficult topics. Additionally, the paper also highlights that vulnerability in the classroom and sharing the difficulties associated with teaching difficult topics can be alleviated by sharing difficulties associated with such instruction.